1998
DOI: 10.1080/03079459808419386
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin and immunity in layer hens

Abstract: A study was conducted on the impact of aflatoxin in the feed on the prophylactic immunization of layer hens against Newcastle disease, infectious bronchitis, infectious bursal disease and fowl cholera. Fourhundred-and-eighty 18-week-old white leghorn chickens were used. Different groups of hens were vaccinated, as per commercial recommendations, with a commercial inactivated triple vaccine against Newcastle disease, infectious bronchitis, and infectious bursal disease. A killed polyvalent bacterin was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 17 publications
(19 reference statements)
1
23
0
1
Order By: Relevance
“…Aflatoxin B1 is carcinogenic to human (IARC, 1993), in chickens, aflatoxin increased susceptibility to, or severity of ceacal coccidiosis, Marek's disease (Edds, 1976), salmonellosis (Smith et al, 1969;Wyatt & Hamilton, 1975), inclusion body hepatitis (Singh et al, 1996), and infectious bursal disease virus (Chang & Hamilton, 1982;Somvanshi & Mohanty, 1991). Vaccination failures were linked to aflatoxicosis in chickens (Anjum, 1994;Pruthi et al, 1992), and impaired response to vaccination responses was demonstrated for Newcastle disease, infectious bronchitis, infectious bursal disease, and fowl cholera (Azzam & Gabal, 1997;Azzam & Gabal, 1998;Bunaciu et al, 1998).…”
Section: Commfmentioning
confidence: 99%
“…Aflatoxin B1 is carcinogenic to human (IARC, 1993), in chickens, aflatoxin increased susceptibility to, or severity of ceacal coccidiosis, Marek's disease (Edds, 1976), salmonellosis (Smith et al, 1969;Wyatt & Hamilton, 1975), inclusion body hepatitis (Singh et al, 1996), and infectious bursal disease virus (Chang & Hamilton, 1982;Somvanshi & Mohanty, 1991). Vaccination failures were linked to aflatoxicosis in chickens (Anjum, 1994;Pruthi et al, 1992), and impaired response to vaccination responses was demonstrated for Newcastle disease, infectious bronchitis, infectious bursal disease, and fowl cholera (Azzam & Gabal, 1997;Azzam & Gabal, 1998;Bunaciu et al, 1998).…”
Section: Commfmentioning
confidence: 99%
“…In layers fed AFB1, age to maturity is increased [34] and egg production is reduced [34,121,125,[128][129][130][131]. Egg quality parameters such as total weight, shape, albumin or yolk percentage, and shell thickness in chickens and quail can be adversely affected by AFB1, although the effects were variable among studies [34,125,126,128,[131][132][133].…”
Section: Production Lossesmentioning
confidence: 99%
“…Esses autores sugerem que o processo inflamatório decorrente da exposição a doses subclínicas de aflatoxinas tenha induzido um discreto aumento na fração das gamaglobulinas. A imunodepressão resultante da ação das aflatoxinas afeta a capacidade da ave em sintetizar anticorpos e substâncias humorais como o interferon, a citocina e as proteínas do sistema complemento, comprometendo a funcionalidade dos leucócitos (AZZAM & GABAL, 1998). As aflatoxinas afetam o perfil imunológico, porém sem suprimir completamente a produção de anticorpos (ZAVIERO & CONTRERAS, 2005).…”
Section: Resultsunclassified